Study on Egg Quality Control Product at PT. X Through The Statistical Quality Control Method Approach - Estefan, Sarah; Al Awwaly, Khothibul Umam; Rosyidi, Djalal (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
PT. X does not implement statistical quality control. This study aims to determine the factors that cause damaged egg products at PT. X, knowing the level of damage to PT. X based on the control chart and corrective actions needed to reduce defective products that meet quality standards. This study uses a descriptive method with a case study approach for 30 working days. Data collection techniques used include observation through manual visual inspection, interviews with staff of PT. X and documentation. This study uses quality control analysis tools in the form of check sheets, histogram diagrams, pareto diagrams, control charts and fishbone diagrams. Controlling the level of damage to egg products at PT. X was outside the control limits, namely 1.99% pale shells, 1.80% cracked shells and 7.09% gross shells of the total production. This research suggests that PT. X implements quality control using the SQC method and applies protectors and dividers to all products to prevent eggs from cracking during storage and distribution as well as routinely removing dirt. PT. X needs to conduct training for production employees so that they can carry out the production process accompanied by inspections in accordance with the company's standard operating procedures.Keywords: eggs, statistical quality control, quality control